Synthesis of Hydroxyapatite-Polyethylene Glycol with In-Situ Method Using Calcium Oxide from Blood Shells (Anadara granosa) - Novesar Jamarun; Nabiila Ayyu Trycahyani; Syukri Arief; Upita Septiani; Vivi Sisca (Indonesian Journal of Chemistry, 2023)
Hydroxyapatite (Ca10(PO4)6(OH)2, HAp) is a calcium phosphate-based biomaterial that is widely used in bone implants due to its similarity in composition with the constituent elements of bone. However, HAp still has poor mechanical properties, so research was carried out to improve the mechanical properties such as reduced brittleness, less fracture resistance, and a denser structure of HAp by synthesizing composites with PEG. This study used PEG as a filler and HAp as a matrix. HAp was synthesized from blood clam shells (Anadara granosa) using the sol-gel method. HAp-PEG composite was synthesized using the in-situ method with various HAp concentrations of 40, 50, 60, 70, and 80%. FTIR characterization showed the presence of functional groups PO43− and CO23−, which indicated the presence of HAp. Analysis of the XRD pattern showed a crystal size of 24.194 nm. SEM-EDX showed the needle-shaped HAp-PEG composite HAp crystal morphology and obtained a Ca/P ratio of 1.87. Analysis of DTA results showed a weight loss of 65.72% in the composite at a temperature > 200 °C. A degradation test was also carried out to see the percentage of the HAp-PEG composite to be degraded, and the optimum degraded composite with increasing days had a concentration of 70%.